Níveis de clorofórmio na água potável distribuída pela estação de tratamento de Boa Vista, Roraima e relação com insuficiência renal - Hayd, Ramão Luciano Nogueira (2011)
The public water supply in terms of quality and quantity is a growing concern of mankind, because of water scarcity and deteriorating quality of water sources. Disinfection is the primary purpose of chlorination and more common, but it appears as the by-products like THMs products of the reaction between chemicals that are used to treat oxidative and organic materials naturally present in water. Chronic kidney disease is currently an important public health problem. In Brazil, the prevalence of patients maintained on welfare programs for the control and treatment of chronic renal failure (CRF) has doubled in recent years. In Boa Vista, Roraima was not carried out any studies regarding THM levels in drinking water by sewage treatment plant. Therefore, it was necessary to identify the levels of chloroform in drinking water and check the possible relation with the incidence of chronic renal failure in the population served by ETA. We use water from the water treatment station in Boa Vista, Roraima, and these were analyzed by Solid Phase Extraction (SPE) and subsequently by spectrophotometry. Our samples were collected in January, February, March, April, May and June 2011 off the Water Treatment Plant for Good. We found the incidence of chronic renal failure in Boa Vista, in the years 2007 to 2009 in billing service General Hospital of Roraima. For the bioassay used adult females, with approximately five weeks, Wistar rats Rattus lineage norvegicusm provided by the vivarium of the Federal University of Mato Grosso do Sul mice at the end of 80 days were sacrificed, kidneys removed and sent to Central Laboratory Roraima to make the slides and histological analysis of renal injury. Obtained concentrations of chloroform in all months analyzed. During the bioassay re-create the conditions where rats ingested different doses of chloroform in drinking water (100 and 300 mg / kg). In our study we developed a new method to construct the analytical calibration curve for chloroform, which is a low-cost market and easy to apply. The proposed method showed good precision and linearity having the interest to the ceilings established by Decree 518/2004 of the Ministry of Health, ensuring the applicability thereof to the simultaneous analysis of chloroform in water intended for human consumption.